Global quantitative proteome analysis of a multi-resistant Klebsiella pneumoniae strain - Illenseher, Marie-Sofie; Hentschker, Christian; Gesell Salazar, Manuela; Busch, Larissa Milena; Zierke, Lisa; Reder, Alexander; Michalik, Stephan; Völker, Uwe; Hammerschmidt, Sven; Surmann, Kristin (Frontiers in Microbiology, 2025)
Klebsiella pneumoniae is a critical nosocomial pathogen with a rising incidence in antibiotic resistance worldwide. Multidrug-resistant strains of K. pneumoniae pose a major health threat, particularly to immunosuppressed and elderly patients. To date, no effective vaccine formulations have been developed. Therefore, the creation of novel therapeutic and preventive treatments is of key importance. Proteins play a central role in host-pathogen interactions, and identifying and characterizing conserved, organism-specific proteins is essential for the creation of novel vaccine formulations. Capsule-deficient K. pneumoniae ATCC BAA-2146Δwza was cultured in minimal medium and exposed to two physiological stress factors to profile its cellular proteome and exoproteome and its adaptation to infection mimicking conditions by mass spectrometry. More than 2,800 proteins covering 54% of the entire annotated proteome, were profiled in untreated controls and after imposition of heat or oxidative stress. The proteomic data revealed that some outer membrane proteins (OMPs), including LPP and other virulence factors involved in iron acquisition and cell wall remodeling, were more abundant in the exoproteome than in the cellular proteome. Approximately one-third of the assigned OMPs were lipoproteins, i.e., proteins that represent important fitness factors and might be immunogenic due to their structure and position in the bacterial cell membrane. In particular, the lipoproteins Pal and SlyB showed the highest abundance among the OM lipoproteins in the intracellular proteome and exoproteome in all tested conditions. These findings suggest that these proteins may be promising candidates for further immunoproteomic analyses to assess their immunogenicity and their role in K. pneumoniae pathogenicity.